A badger in Bannerghatta: an opportunistic record of the Ratel Mellivora capensis (Schreber, 1776) (Mammalia: Carnivora: Mustelidae) from Karnataka, India - Avinash Krishnan; Sunil Panwar; Aaranya Gayathri; Sagarika Phalke; Dilip Abani Venkateshaiah (Journal of Threatened Taxa, 2016)
A single observation of a Ratel Mellivora capensis has been photo-documented in Bannerghatta National Park on 2 November 2015. This record being the first contemporary evidence of badgers in this region of Karnataka, India, the paper also presents a case study of badgers being close to a highly human-dominated landscape which could be due to some ecological factors that may be conducive as a habitat within the Park. Though a resident population and distribution within the BNP could not be ascertained, it can be proposed that the region may be an extension of range of its most recently documented distribution in the Eastern Ghats landscape.